2018
DOI: 10.1093/jac/dky127
|View full text |Cite
|
Sign up to set email alerts
|

Increased antibiotic resistance exhibited by the biofilm of Vibrio cholerae O139

Abstract: The biofilm of V. cholerae O139 was found to be resistant to different types of antibiotics tested. This unconventional biofilm resistance highlights the hidden danger of antimicrobial escape by V. cholerae, increased risk of cholera transmission and its continued persistence in the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Here also results suggest that the ripe seed extract is more effective as biofilm eradication agent as they could show significant higher percentage of eradication of preformed biofilm ( P <0.05) at all the concentrations than unripe seed extract. MBEC of vancomycin against S. aureus is > 256 µg/mL [ 87 ] and that for doxycycline is 32 µg/mL against V. cholerae [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here also results suggest that the ripe seed extract is more effective as biofilm eradication agent as they could show significant higher percentage of eradication of preformed biofilm ( P <0.05) at all the concentrations than unripe seed extract. MBEC of vancomycin against S. aureus is > 256 µg/mL [ 87 ] and that for doxycycline is 32 µg/mL against V. cholerae [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…MIC and MBC values of vancomycin against S. aureus are 1.0 and 2.0 µg/mL, respectively [ 87 ]. Whereas, MIC and MBC values of doxycycline against V. cholerae are 0.25 and 2 µg/mL respectively [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since it has reported that bio lm can protect bacterial cells from antibiotic pressure, we intend to see if resveratrol can increase the bactericidal activity of polymyxin B against the cells with established bio lm [30][31] . In this experiment, bio lm was cultivated with the isolate PA2, which has the highest bio lm formation capability, and bio lm in uence on the sensitivity of this isolate to polymyxin B was measured by comparing the growth of bacteria with or without established bio lm.…”
Section: Resveratrol Increases Bactericidal Activity Of Polymyxin B A...mentioning
confidence: 99%
“…cholerae expresses several survival strategies to adapt to acidic and oxidative conditions. Aggregation (or suspended biofilms) and biofilm formation have been reported to physically protect V. cholerae from acid stress (Zhu and Mekalanos, 2003) due to the strong protection given by the biofilm matrix that protects V. cholerae from various stressors, including antibiotics and ROS (Mankere et al, 2018;Wang et al, 2018). Another mechanism providing resistance to low pH is the activation of the acid tolerance response (ATR).…”
Section: Low Phmentioning
confidence: 99%